2022
DOI: 10.3390/insects13100857
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dust and Wettable Powder Formulation of Diatomaceous Earth (Detech®) in the Control of Tyrophagus putrescentiae (Schrank) (Acari: Acaridae)

Abstract: Tyrophagus putrescentiae (Schrank) (Acari: Acaridae) is a cosmopolite mite species commonly in found food and stored products. In this study, the acaricidal activity of two Turkish diatomaceous earth (DE) formulations (Detech® WP95 and Detech® Dust) were applied on a concrete surface at five different concentrations (1, 2.5, 5, 7.5, and 10 g/m2) and dead individuals were counted at 11 different time intervals (1, 3, 6, 9, 12, 15, 18, 21, 24, 27, and 30 h) at a temperature of 25 ± 1 °C and 75 ± 5% relative humi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The cuticle characteristics of the insect species to which DE is applied affect its susceptibility to DE (Athanassiou et al, 2005). Studies have shown that diatomaceous earth will damage the cuticles of soft-bodied organisms such as mites more quickly, so mites will have a higher mortality rate in a shorter period than insects (Kılıç, 2022). In this study, DE was used mixed with water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cuticle characteristics of the insect species to which DE is applied affect its susceptibility to DE (Athanassiou et al, 2005). Studies have shown that diatomaceous earth will damage the cuticles of soft-bodied organisms such as mites more quickly, so mites will have a higher mortality rate in a shorter period than insects (Kılıç, 2022). In this study, DE was used mixed with water.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DE was used mixed with water. However, Kılıç (2022) tested the dust formulation of DE. The results obtained from this study show that both the species and the formulation types of DE are significant in effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mites are considered one of the most abundant groups of pest arthropods (Howard et al, 2001;Athanassiou et al, 2005;Stejskal &Hubert, 2008 andKilic, 2022). In addition to immediately harming the stored goods and lowering their nutritional content (Boczek, 1991 andKrantz, 1955), a large number of mite species in preserved food and its derivatives can also trigger allergic reactions in people (Kondreddi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%